La conformación del Consejo de Defensa Suramericano y su impacto en la concepción de la seguridad externa en el Ecuador, del 2008 al 2012 - Pico Guevara, Pablo Lenin (2017)
Given the imminent failure of the Hemispheric Collective Security model, with the initiative and interest of Brazil, the South American Defense Council emerges, as a mechanism for political dialogue and cooperation in defense matters, no longer based on the traditional condition of “balance of powers”, but founded under the principles of Liberalism as the promotion of regional peace through the generation of mutual trust, interdependence and peaceful settlement of disputes. In Ecuador, the creation of this organization has contributed to a better understanding with neighboring States, generating stable relations, fostering cooperation and healing old wounds caused by border conflicts or sovereignty violations. In the military sphere, the orientation to external security has been reduced, in favor of internal security operations, fight against new threats and support for State action; However, changes in the strategic political level of defense have not transcended the military strategic, operational and tactical levels, mainly due to a lack of communication channels between the Ministry of Defense and the Armed Forces. Despite its liberal orientation, the SDC will always be influenced by the Realism theories, where the conflict seems imperishable and in which the ideologists of its implementation, do not remove the possibility of converting it into a military alliance for the defense of the natural resources of the region.